Abdominal ultrasound in the diagnosis of cerebrospinal fluid pseudocysts complicating ventriculoperitoneal shunts. Issue 7 (July 1984) - Briggs, J R; Hendry, G M; Minns, R A
Abstract : Pseudocysts filled with cerebrospinal fluid caused complications at the distal end of ventriculoperitoneal shunts in five children. Only one of these cysts was infected. The children presented with raised intracranial pressure or abdominal symptoms, or both. We report on the usefulness of abdominal ultrasound examination in the diagnosis and follow up of these patients and suggest that abdominal ultrasound should form part of the initial assessment of children with ventriculoperitoneal shunt dysfunction.